Minda Melayu baharu - Siddiq Fadzil, Dato', 1947-2021; Hanif Ahmad Baharuddin (Shah Alam, Selangor : IDE Research Centre Sdn. Bhd., 2022)
On Islam and state in Malaysia.
Keywords: Malays (Asian people) -- Malaysia; Islam -- Malaysia